Switzerland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper examines economic growth in Switzerland. It attempts to analyze whether slow growth is inescapable for Switzerland. The paper suggests that income convergence across countries contributes significantly to slow relative growth in Switzerland, but experience in several advanced industrial countries reinforces the view that slow growth is not inescapable. Higher growth will require raising total factor productivity growth, which remains low by international standards, and to a lesser extent, raising the investment rate.